Pengaruh literasi keuangan syariah, religiusitas, dan karakteristik demografi terhadap minat gen z dalam melakukan transaksi di bank syariah kota malang - Istianah, Nur (Maliki Interdisciplinary Journal, 2025)
<div id="tw-container" class="nev7se" data-cp="1" data-nnttsvi="1" data-ntl-fpwrite="true" data-sletp="false" data-sm="1" data-ssbp="false" data-sugg-time="500" data-sugg-url="https://clients1.google.com/complete/search" data-uilc="en" data-vil=",af,af-ZA,am,am-ET,ar-EG,ar-AE,ar-KW,ar-QA,ar,ar-IL,ar-JO,ar-LB,ar-PS,az,az-AZ,bg,bg-BG,bn,bn-BD,bn-IN,ca,ca-es,cs,cs-CZ,de,de-DE,de-CH,de-AT,de-LI,en,en-US,en-CA,en-AU,en-NZ,en-GB,en-IN,en-KE,en-TZ,en-NG,en-GH,en-PH,en-ZA,es,es-ES,es-AR,es-UY,es-419,es-BO,es-CL,es-CR,es-CO,es-DO,es-EC,es-GT,es-HN,es-NI,es-PA,es-PE,es-PR,es-PY,es-SV,es-VE,es-MX,es-US,eu,eu-ES,fi,fi-FI,fr,fr-FR,fr-CH,fr-BE,gl,gl-ES,gu,gu-IN,he,he-IL,iw,iw-IL,hu,hu-HU,hy,hy-AM,id,id-ID,is,is-IS,it,it-IT,it-CH,ja,ja-JP,jv,jv-ID,ka,ka-GE,km,km-KH,kn,kn-IN,ko,ko-KR,la,lo,lo-LA,lv,lv-LV,ml,ml-IN,mr,mr-IN,ms,ms-MY,nl,nl-NL,nb,nb-NO,ne,ne-NP,pl,pl-PL,pt,pt-BR,pt-PT,ro,ro-RO,ru,ru-RU,si-LK,sk,sk-SK,sr,sr-RS,su,su-ID,sv,sv-SE,sw,sw-TZ,sw-KE,ta,ta-IN,ta-SG,ta-LK,ta-MY,te,te-IN,tr,tr-TR,ur,ur-PK,ur-IN,yue,yue-HK,yue-Hant-HK,zh-HK,zh,zh-CN,zh-cmn,zh-cmn-CN,zh-Hans,zh-Hans-CN,zh-cmn-Hans,zh-cmn-Hans-CN,cmn-CN,cmn-Hans,cmn-Hans-CN,zh-TW,zh-Hant-TW,cmn-TW,cmn-Hant-TW,zh-cmn-TW,zh-cmn-Hant-TW,zu,zu-ZA,hi,hi-IN,tl,tl-PH,pa,pa-IN"> This study aims to analyze the influence of Islamic financial literacy, religiosity, and characteristics on the demographics of Generation Z’s interest in transacting at Islamic banks in Malang City. Generation Z is an age group that grew up in the digital era who has an interest in technology, ethics and sustainability in financial decision making. The approach used is quantitative with a survey as a data collection method, this study involved 30 respondents who met the inclusion criteria. The results of the regression analysis show that Islamic financial literacy, religiosity, and demographic characteristics have a significant influence on transaction interest individually and through interaction variables. This approach provides an important overview for developing more effective marketing and education strategies for Islamic banks.